2019
DOI: 10.1108/ijccsm-04-2018-0030
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and crop farming in Bangladesh: an analysis of economic impacts

Abstract: Purpose-Changes in climate may have both beneficial and harmful effects on crop yields. However, the effects will be more in countries whose economy depends on agriculture. This study aims to measure the economic impacts of climate change on crop farming in Bangladesh. Design/methodology/approach-A Ricardian model was used to estimate the relationship between net crop income and climate variables. Historical climate data and farm household level data from all climatic zones of Bangladesh were collected for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…Bozzola et al (2017) point to the fact that farm incomes are very sensitive to seasonal changes in temperature and precipitation, whereas farms with an irrigation system have the main advantage in this regard. Similar results are obtained by Hossain et al (2019), when farmers' incomes are influenced mainly by the temperature and the ability of agricultural holdings to use irrigation equipment. The results show that the implementation of global models on climate change can have an impact on income growth in this area, namely by 25-84 USD per hectare.…”
Section: Introductionsupporting
confidence: 80%
“…Bozzola et al (2017) point to the fact that farm incomes are very sensitive to seasonal changes in temperature and precipitation, whereas farms with an irrigation system have the main advantage in this regard. Similar results are obtained by Hossain et al (2019), when farmers' incomes are influenced mainly by the temperature and the ability of agricultural holdings to use irrigation equipment. The results show that the implementation of global models on climate change can have an impact on income growth in this area, namely by 25-84 USD per hectare.…”
Section: Introductionsupporting
confidence: 80%
“…Further, the research done by Pickson et al, (2020) explored the nexus of climate change and cereal production for China for 1990Q1-2013Q4 using the ARDL, Johansson cointegration, and Granger causality test have found that CO2e and average temperature severely affected cereal production, whereas average rainfall, cultivated area, and agricultural worker significantly enhanced cereal production in both short-term and long-term. Hossain et al (2019) reveal that climate change can have both beneficial and harmful effects on agricultural sector in Bangladesh. The net crop income in the country was seen to vary with the rise in temperature in areas with extensive irrigation facilities.…”
Section: Climate Change and Agriculturementioning
confidence: 99%
“…In response to the decline in the country's major crop's productivity due to climate change, the agriculture sector is seeing an increase in crop diversification [10]. Cotton cultivation could play an important role in this shift in cropping patterns.…”
Section: Introductionmentioning
confidence: 99%